A first insight into seropositivity and risk factors for Brucella spp. and Coxiella burnetii in free-roaming dogs in Ecuador - Angel Sebastian Rodriguez-Pazmiño; Carla M. Brito; Mauricio Salas-Rueda; Solon Alberto Orlando; Miguel Angel Garcia-Bereguiain (One Health)
Brucellosis and Q fever are two bacterial zoonoses caused by Brucella spp. and Coxiella burnetii, respectively. Dogs are reservoirs of these pathogens and play an important role in their spread. In this research, we determined the seroprevalence of antibodies against Brucella spp. and C. burnetii in free-roaming dogs from Ecuador and conducted a statistical analysis based on geographical variables. Serum samples were collected from 397 free-roaming dogs between November 2018 and May 2019 and analyzed with commercial ELISA tests for Brucella spp. and Q fever. An overall seroprevalence of 2.8 % (CI: 95 %, 0.0–6.2 %) and 1.8 % (CI: 95 %, 0.0–5.6 %) was found for Brucella spp. and C. burnetii, respectively. No statistical differences in seroprevalence values were found between geographical regions in Ecuador or between dogs from rural or urban settings, except for the association of C. burnetii infection with the Coastal Region. This is the first study of this kind in Ecuador and points out the need for a One Health approach for control and surveillance of zoonotic diseases like brucellosis and Q fever including feral and stray dogs as reservoirs to spread those pathogens to cattle, humans, or wildlife.